1994
DOI: 10.1111/j.1432-1033.1994.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Domain of the Epidermal Growth Factor Receptor

Abstract: The binding of epidermal growth factor (EGF) or an EGF-like growth factor to the EGF receptor is the initial event which leads to receptor activation, and consequently the induction of cell growth. In order to study this binding interaction in detail, we produced the extracellular domain of the EGF receptor (EGFR) using the baculovirus expression system. Affinity-labeling and Western-blot analyses revealed that the baculovirus-infected insect cells secrete active EGFR extracellular domain relatively efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 40 publications
(36 reference statements)
9
39
0
Order By: Relevance
“…Two sEGFR populations have been detected in solution: one with a high a nity (2 ± 20 nM) and the other with a low a nity (400 ± 550 nM) for EGF (Domagala et al, 2000). The results of these studies are complicated by the fact that some groups have used soluble receptor fragments, while others have used full-length receptor present on the surface of intact cells; the a nity of EGF for a soluble extracellular EGFR fragment has been shown to be markedly lower than for the full-length receptor (Brown et al, 1994). Furthermore, interpretation of binding studies with erbB receptors must take into account that the receptors are in a monomer/oligomer equilibrium which is not governed solely by ligand concentration.…”
Section: Ligand-dependent Dimerizationmentioning
confidence: 82%
See 1 more Smart Citation
“…Two sEGFR populations have been detected in solution: one with a high a nity (2 ± 20 nM) and the other with a low a nity (400 ± 550 nM) for EGF (Domagala et al, 2000). The results of these studies are complicated by the fact that some groups have used soluble receptor fragments, while others have used full-length receptor present on the surface of intact cells; the a nity of EGF for a soluble extracellular EGFR fragment has been shown to be markedly lower than for the full-length receptor (Brown et al, 1994). Furthermore, interpretation of binding studies with erbB receptors must take into account that the receptors are in a monomer/oligomer equilibrium which is not governed solely by ligand concentration.…”
Section: Ligand-dependent Dimerizationmentioning
confidence: 82%
“…A general scheme based on current understanding of EGF induced oligomerization is shown in Figure 2. Multiple studies have concluded that EGF binds EGFR with a 1 : 1 stoichiometry (Brown et al, 1994;Domagala et al, 2000;Lemmon et al, 1997;Odaka et al, 1997;Weber et al, 1984). Subdomains I and especially III of the extracellular portion of EGFR have been identi®ed as important in ligand binding (Lax et al, 1998(Lax et al, , 1989Lee et al, 1995;Summer®eld et al, 1996), as has subdomain IV, one of two cysteine rich domains (Saxon and Lee, 1999).…”
Section: Ligand-dependent Dimerizationmentioning
confidence: 99%
“…The immunoprecipitates were then washed four times in cold PBS containing 0.1% Tween-20, resuspended in SDS sample bu er, boiled for 5 min and pelleted by centrifugation at 2000 g for 1 min. The eluate was loaded onto a 7.5% SDS-polyacrylamide gel, transferred to nitrocellulose (Costar, Cambridge, MA, USA), blocked overnight in PBS containing 3% dried milk, then incubated with polyclonal antibody against EGFR (Brown et al, 1994), erbB-2 (C-18, Santa Cruz Biotechnology), erbB-3 (C-17, Santa Cruz Biotechnology), or erbB-4 (C-18, Santa Cruz Bio-technology), or monoclonal anti-phosphotyrosine (clone 4G10, Upstate Biotechnology Inc., NY, USA). Blots were developed using the alkaline phosphatase substrate detection kit from Vector Laboratories (Burlingame, CA, USA).…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…It has been shown that the amino acid residues in the EGFR that are essential for binding the LA22 monoclonal antibody (Ala 351 -Asp 364 ) are not critical for the binding of EGF or TGF-␣ because the epitope was eliminated, whereas ligand binding was unaffected (77). Thus, because the monoclonal antibody is bulky it is likely that the EGF binding site is located in the near vicinity and that the competition with EGF occurs by steric hindrance.…”
Section: Fig 6 Decorin and Egf Bind To A Finite Region Within The Lmentioning
confidence: 99%